Infection of Red Deer, Cattle, and Humans with Mycobacterium bovis subsp. caprae in Western Austria - Prodinger, Wolfgang M. (American Society for Microbiology, 2002)
Twelve cases of Mycobacterium bovis subsp. caprae infection have occurred in four humans, three cattle, and five red deer in western Austria since 1994. DNA-fingerprinting of the isolates suggested transmission in and between these species over several years. Contact with cattle, but not with goats, was found to be associated with three of four human cases.